What is Liquid? - Henderson, D.; Holovko, M.; Nezbeda, I.; Trokhymchuk, A. (Condensed Matter Physics, 2015)
The idea of this special issue was derived a year ago. The year 2014 was a significant anniversary both generally and personally. Personally, it was 80 years since the oldest of us, Douglas Henderson, was born. More generally, it was a hundred years since another important paper in the theory of liquids by Ornstein and Zernike appeared. With this in mind, we felt it is timely for a collection of expert contributions to fill at least some of the gaps on the way to answer that magic question What is "liquid"? We are thankful for all colleagues who joined us in this project.